Epibiont Assemblages on Nesting Hawksbill Turtles Show Site-Specificity in the Persian Gulf - Loghmannia, Javad; Nasrolahi, Ali; Rezaie-Atagholipour, Mohsen; Kiabi, Bahram H. (Frontiers in Ecology and Evolution, 2021)
Sea turtle epibionts can provide insights into the hosts' habitat use. However, at present, there is a lack of information on sea turtle epibiont communities in many locations worldwide. Here, we describe the epibiont communities of 46 hawksbill turtles (Eretmochelys imbricata) in the Persian Gulf. Specifically, we sampled 28 turtles from the Dayyer-Nakhiloo National Park (DNNP) in the northern Gulf and 18 turtles from Shibderaz beach in the Strait of Hormuz. A total of 54 macro, meio, and micro-epibiont taxa were identified, including 46 taxa from Shibderaz and 29 taxa from DNNP. The barnacles Chelonibia testudinaria and Platylepas hexastylos, as well as harpacticoid copepods and Rotaliid foraminifers, had the highest frequency of occurrence found on almost all turtle individuals. Harpacticoids were the most abundant epizoic taxa (19.55 ± 3.9 ind. per 9 cm2) followed by forams (Quinqueloculina spp.: 6.25 ± 1.5 ind. per 9 cm2 and Rotaliids: 6.02 ± 1.3 ind. per 9 cm2). Our results showed significant differences between the study sites in the composition of micro and macro-epibiont communities found on hawksbill turtles. We speculate that the differences in epibiont communities were largely influenced by local environmental conditions.